Effects of Antibiotic Treatment on the Results of Nested PCRs for Scrub Typhus - Kim, Dong-Min (American Society for Microbiology (ASM), 2008)
In order to determine the effects of antibiotic treatment on the results of nested PCRs for scrub typhus, we investigated the frequency of positive outcomes at various times after antibiotic administration in patients with scrub typhus. The rate of detection by nested PCR with blood buffy coat before antibiotic administration was 90.5%. However, this decreased to 60.5% within 3 days after administration of antibiotics such as doxycycline and rifampin and to 10% by the fourth day following antibiotic administration. Since the sensitivity of nested PCR can be affected by antibiotic administration, clinicians should perform this PCR before antibiotic administration and at the latest within 3 days after antibiotic administration.